2014
DOI: 10.3390/molecules19068289
|View full text |Cite
|
Sign up to set email alerts
|

A PPARγ, NF-κB and AMPK-Dependent Mechanism May Be Involved in the Beneficial Effects of Curcumin in the Diabetic db/db Mice Liver

Abstract: Turmeric (Curcuma longa) is a rhizomatous herbaceous perennial plant of the ginger family which has been used to treat biliary disorders, anorexia, cough, rheumatism, cancer, sinusitis, hepatic disorders, hyperglycemia, obesity, and diabetes in both Ayurvedic and Traditional Chinese Medicine. Suggested mechanisms of action include the modulation of signal transduction cascades and effects on gene expression, however they remain to be elucidated. In this study, the expression of some proteins responsible for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 56 publications
1
96
0
Order By: Relevance
“…Multiple mechanisms, like decreased macrophage accumulation in WAT, down-regulation of proinflammatory cytokines and increase in adiponectin levels, are exhibited by curcumin for improving insulin sensitivity [29]. Curcumin increased the expression of AMPK in diabetic db/db mice, which might be a possible mechanism in suppressing hepatic glucose production, resulting in decreased blood glucose levels [30]. Curcumin exhibits cytoprotective mechanisms increasing levels of key mitochondrial biogenesis-regulating transcription factors like PGC-1α, nuclear respiratory factor-1 and mitochondrial transcription factor A [31].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms, like decreased macrophage accumulation in WAT, down-regulation of proinflammatory cytokines and increase in adiponectin levels, are exhibited by curcumin for improving insulin sensitivity [29]. Curcumin increased the expression of AMPK in diabetic db/db mice, which might be a possible mechanism in suppressing hepatic glucose production, resulting in decreased blood glucose levels [30]. Curcumin exhibits cytoprotective mechanisms increasing levels of key mitochondrial biogenesis-regulating transcription factors like PGC-1α, nuclear respiratory factor-1 and mitochondrial transcription factor A [31].…”
Section: Discussionmentioning
confidence: 99%
“…In short, this molecule has a beneficial effect for treatment of diabetic complications via the regulation of the expression of AMPK, PPARγ, and NF-κB (Jimenez-Flores et al, 2014). In another study, curcuminoids have been reported to induce the modulatory subunit of gamma-glutamyl-cysteine ligase; expression of heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 at both the mRNA and protein levels in human islets.…”
Section: Effect Of Curcumin On Pancreaticߚ-cell Dysfunctionmentioning
confidence: 95%
“…SDS-PAGE and western blot were performed as previously described [12]: 30 μg of placenta lysate was separated on 10% polyacrylamide gel, and resolved proteins were transferred to nitrocellulose membrane. Molecular weights were identified by comparison with the motility of pre-stained protein standards (Precision Plus Protein Standards, Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%